ESTIMATION ANALYSIS OF CARBON DIOXIDE (CO2) EMISSIONS FROM MOTOR VEHICLES IN THE MAJOR ROAD PAYAKUMBUH CITY - Wahyudi, Doni
Carbon Dioxide (CO2) is one of the highest emission compounds produced from burning fossil fuels from combustion engine motor vehicles and is considered a major contributor to the greenhouse effect. Nearly 70% of urban air pollution is caused by motor vehicle activity. The greenhouse effect makes the earth warmer which affects the world's climate with the impact of several disasters such as floods, landslides and sea level rise. Besides other impacts on humans such as disruption of health, economic impacts and social impacts. Payakumbuh City is the third largest city in West Sumatra Province also experiencing the same problems with other cities in Indonesia. As cities grow and develop, traffic and congestion of motorized vehicle traffic will cause negative effects, such as increased emissions of carbon dioxide (CO2). For this reason it is deemed necessary to know the estimated amount of production and the projected increase in the next few years from the CO2 emissions generated by motor vehicles in the road network, especially the main roads in the City of Payakumbuh. It is important to know that related institution, for planning and make policies, especially in the field of transportation that continues to support the growth of the city by minimizing the impact on the environment, economy and social with the concept of sustainable transportation, that aims to reduce air pollution. By knowing the quantity of vehicle volumes per road section and the rate of increasing, the amount of CO2 emission production can be calculated quantitatively using the emission factor per type of vehicle and vehicle mileage. The results of the analysis of the amount of CO2 production are calculated in units of ppm / day and described spatially with the ArcGIS software on the map of Payakumbuh City in the span of five years from 2019 to 2039.iv Total production of CO2 emission in 2019 for several main roads and alternative roads within the scope of the study was 22,002.72 x106 ppm / day, grow to 58,714.27 x106 ppm / day in 2039 with a growth rate of 5.03% per year. Soekarno Hatta Road is the largest road section that produces CO2 emissions and motorbikes are the largest types of vehicles that produce CO2 emissions.